127k views
5 votes
Solve: 4x(x - 3)(x + 5)(2x - 7) = 0

1 Answer

3 votes

Answer: 8x⁴ - 12x³ - 176x² + 420x

Explanation:

First multiply 4x by (x - 3) which = 4x² - 12x. Next multiply (4x² - 12x) by (x + 5) which = 4x³ + 8x² - 60x. Multilying our new trinomial with the next binomial: (4x³ + 8x² - 60x)(2x - 7) = 8x⁴ + 16x³ - 120x² - 28x³ - 56x² + 420x. Combining like terms: 8x⁴ - 12x³ - 176x² + 420x. Notice that when you reduce and factor, you will end up with the starting binomials meaning this solution is correct.

User Alisonthemonster
by
6.1k points